Mechanical Research of Reinforced Concrete Materials - Wang, Wei (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
"Mechanical Research of Reinforced Concrete Materials" describes the mechanical properties of reinforced concrete materials. The topics include theoretical, experimental and numerical studies, to evaluate the general deformation response, damage evolution and failure patterns of ordinary and high-performance reinforced concrete materials under various loading conditions (e.g., quasi-static, dynamic, fatigue, and impact).